The complexity and structural diversity of ant venom peptidomes is revealed by mass spectrometry profiling. (28th January 2015) - Touchard, Axel; Koh, Jennifer M. S.; Aili, Samira R.; Dejean, Alain; Nicholson, Graham M.; Orivel, Jérôme; Escoubas, Pierre
Abstract : Rationale: Compared with other animal venoms, ant venoms remain little explored. Ants have evolved complex venoms to rapidly immobilize arthropod prey and to protect their colonies from predators and pathogens. Many ants have retained peptide‐rich venoms that are similar to those of other arthropod groups. Methods: With the goal of conducting a broad and comprehensive survey of ant venom peptide diversity, we investigated the peptide composition of venoms from 82 stinging ant species from nine subfamilies using matrix‐assisted laser desorption/ionisation time‐of‐flight mass spectrometry (MALDI‐TOFMS). We also conducted an in‐depth investigation of eight venoms using reversed‐phase high‐performance liquid chromatography (RP‐HPLC) separation coupled with offline MALDI‐TOFMS. Results: Our results reveal that the peptide compositions of ant venom peptidomes from both poneroid and formicoid ant clades comprise hundreds of small peptides (<4 kDa), while large peptides (>4 kDa) are also present in the venom of formicoids. Chemical reduction revealed the presence of disulfide‐linked peptides in most ant subfamilies, including peptides structured by one, two or three disulfide bonds as well as dimeric peptides reticulated by three disulfide bonds. Conclusions: The biochemical complexity of ant venoms, associated with an enormous ecological and taxonomic diversity, suggests that stinging ant venoms constitute a promising source of bioactive molecules that could be exploited in the search for novel drug and biopesticide leads. Copyright © 2015 John Wiley & Sons, Ltd.